Combustion visualization and measurement in a closed vessel - Aznam, Siti Nur Amalina (2015)
In accessing the research of burning velocity, it was found that a wide range of determination on burning velocity by pressure record method and schlieren photography technique research exists. Both method has been observed broadly in expanding spherical flame in gaseous phase. Therefore various oxidizer-fuel mixture comparison were made based on their accuracy. However, in the author’s knowledge there has not been an extensive experimental data develop locally. Thus a gap exists for further research in this area. A cylindrical vessel combustor that correspond to spherically expanding flame is used in this experiment. The experiment is subjected for only premixed methane-air of five equivalence ratio (?) which are lean (0.7, 0.8), stoichiometric (1.0) and rich (1.2, 1.4). The maximum pressure recorded was examined. Simultaneously a schlieren photography technique was employed during the combustion at stoichiometric condition. The schlieren image provide the visualization of the propagating flames. The result of pressure profile at stoichiometry condition was compared with the previous work by other researcher. Based on the experimental investigation, the trend line of the recorded pressure profile and the burning velocity at various equivalence ratio in this experiment is similar as obtain in previous work done. The burning velocity of premixed methaneair were 6.328 cm/sec for ? =0.7, 9.718 cm/sec for ? =0.8, 26.415 cm/sec for ? =1.0, 18.081 cm/sec for ? =1.2 and 5.026 cm/sec for ? =1.4 respectively.